Understanding parenting responsibilities as a challenge to mental healthcare access for mothers with a mental illness in Tyrol, Austria - Monika Schamschula; Annette Bauer; Jean Lillian Paul (Elsevier, 2024)
It is estimated that one out of three individuals will experience a mental illness at some point in their lives. Parenting with a mental illness can be particularly challenging and often requires additional support and resources to navigate through it. One of the challenges is accessing mental healthcare while also having parenting responsibilities. This study aims to explore how mothers with a mental illness in Tyrol, Austria, experience the impact of their parenting responsibilities in terms of accessing mental healthcare, and which processes contribute to such challenges. We draw from 20 semi-narrative interviews with mothers with a mental illness which were conducted in the context of a larger research project, focusing on developing and evaluating support for families with a parent with a mental illness. We identified three main findings affecting access to mental healthcare services: (1) organisational issues with mental healthcare services, (2) socio-cultural norms around family and care work, and (3) identity-related expectation of being a 'good mother' who is always there for her children. The concern for the children's wellbeing was also closely linked to these aspects. It is important, however, to consider the ways in which these findings are interwoven, and that social support could mitigate challenges. The findings of this study contribute to understanding childcare responsibility as a significant challenge to accessing mental healthcare for mothers with a mental illness and recognising it as a structural, socio-cultural, and identity-related phenomenon.